Services R&D - Jeremy Howells (European Commission, Joint Research Centre (JRC), 2009)
This document analyses the nature of service R&D activity and growth. The role and significance of R&D in services has been growing rapidly recently, although in the context of services it is also important to note that much innovative activity in the service sector remains of a non-R&D and non-technological nature. Thus, services are becoming more research intensive over time and the significance of innovation to their performance is also increasingly being recognised.
Keywords: O33; 330; R&D in services sectors; trends